Protection of Private Rights to Copyright Portraits of Silhouette - Fajar Tri Septiono; Budi Hermono (NOVUM : JURNAL HUKUM, 2024)
The portrait is copyrighted works protected by the Copyright Law. The problem raised in this study is that when a portrait is taken by a photographer, which is no visible face of the person being photographed. The purpose of this research is to analyze whether the object in the portrait but only in silhouette has a private right to copyright. The portrait to be studied is a portrait entitled "A Farmer's Quiet Journey". The method used is legal research at the legal dogmatic level. Legal research is a process to identify, analyze problems, then solve problems that exist. The results of this study indicate that the portrait with the title "A Farmer's Quiet Journey " contains the object of the person in it, although there is no visible face as identification of the person being photographed, it can still be detected that an object is a person, so the photographic work is assumed to be a portrait. Thus, the person in the portrait has private rights to the copyright of his portrait. Therefore, uploading it at Adobestock still has to be with the permission of the person who owns the silhouette